(3JfbjM GdefGXQs - (3ceGd GdOjf MSf GdaGQSjs ((3fjSGHhQ s)
(3ChdgG (B:s
(3GdMeO ddg fhQ GdCfhGQ heXgQ YLGFH GdCSQGQ hGgH GdSeY hGdCHUGQ hechQ GdfgGQ Ydi Gddjd hMchQ Gddjd Ydi GdfgGQ hHYO abO LGAfi Ydi ef JfhQ YbdI s
(3BNQgG (B:s
(3heG hLO ef dhfG GdbHjd jbJVi VYa GdZQjRI hbdI GdHVGYI adfNJe GdcJGH MGeOjf Gddg SHMGfg hJYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs